Aspectos reprodutivos e moleculares de Pimelodus maculatus – LACÈPÉDE 1803 (Siluriformes pimelodidae) - Moreira, Roosevelt Gonçalves (2007)
Many species of Neotropical fish fact this that comes being deeply affected for the construction of dams for hydroelectric plants. Trying to solve the problem, one of the options is to promote the reproduction artificial of the related species. The success of the sex reproduction depends on many factors, mainly the related ones to sperm cell and, as for the male, is distinguished referring aspects to the semen, a time that of it depends the fertilizing capacity on the spermatozoon. In this context the present work objectified to effect the hormonal induction of the mandi-yellow (Pimelodus maculatus) using itself the inoculations of pituitary extract and also to verify the influence of different values of pH on the time of motility of the spermatozoon of the related species. All the animals had positive reply to the hormonal treatment. The sex maturity allowed the visualization of sex dimorphism. The variations of pH had not significantly intervened with the motility of the spermatozoa of Pimelodus maculatus.